ChemInform Abstract: Cobalt Nitrides as a Class of Metallic Electrocatalysts for the Oxygen Evolution Reaction. Issue 18 (April 2016) - Chen, Pengzuo; Xu, Kun; Tong, Yun; Li, Xiuling; Tao, Shi; Fang, Zhiwei; Chu, Wangsheng; Wu, Xiaojun; Wu, Changzheng
Abstract: Co2 N, Co3 N, and Co4 N are prepared by nitridation of the precursors β‐Co(OH)2 (380 °C, 2 h), α‐Co(OH)2 (380 °C, 2 h), and Co3 O4, resp., under flowing NH3 (420 °, 2 h).